A simulation study on specific cases of reentrant-line systems - Matias, Aura C.; Daway, Rhey David S.
A reentrant line is a queueing network wherein work-in-process materials (WIP) pass through one or more stations several times before eventually leaving the system. Determining the scheduling mechanism that optimizes system performance is a common concern in reentrant-line configurations. A study by Daway and Matias proposed an inventory control policy, called the Bounded Inventory Level Policy (BILP), which attempts to strike a balance between the frequency of setups and the variability in the internal flow processes for the purpose of reducing the long run average total holding cost per unit output. The mathematical analysis exhibited cases wherein BILP is superior to existing inventory control policies. A simulation study was conducted on specific cases of reentrant line systems with the same objectives as those of the analytical study.
Keywords: Bounded inventory level policy; Reentrant lines; Scheduling policies